Halal Industry in Madura: Development Model and Strategy - Rum, Mokh. (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
Madura has potential for Halal products. The four districts each have superior products with export potential. The development of the halal industry is an alternative to increasing the contribution of superior products to the regional economy and people's income. Its development requires the synergy of stakeholders through the Penta Helix model. This research aims to: 1). formulating the Penta Helix synergy model in the development of the halal industry in Madura; 2). formulate strategic priorities for the development of the halal industry in Madura. This research was conducted in Bangkalan Regency, Madura from September to November 2022. Data analysis for developing the Penta Helix model used a qualitative descriptive approach, while determining the priority of the development strategy for the Madura halal industry using the Analytical Hierarchy Process (AHP). Respondents in this study are experts in the development of the halal industry.              The Penta Helix model in this study is a collaborative design and relationship between five elements consisting of academia, government, farmers and fishermen, halal industry players, and the community. The Penta Helik collaboration is very important for the development of the halal industry in Madura, but so far the institution has not been built, so this research recommends that a business partnership should be designed. The results of the AHP analysis show that the main criteria in determining the strategy for the development of the halal industry are institutions. The recommended strategy isPenta Helix collaboration.The institutional design of the Penta Helix partnership and collaboration is the main prerequisite that must be carried out for the development of the halal industry in Madura.